2013
DOI: 10.1155/2013/405743
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gene-Gene and Gene-Environment Interactions on the Risk of Asbestosis

Abstract: This study investigated the influence of gene-gene and gene-environment interactions on the risk of developing asbestosis. The study comprised 262 cases with asbestosis and 265 controls with no asbestos-related disease previously studied for MnSOD, ECSOD, CAT, GSTT1, GSTM1, GSTP1, and iNOS polymorphisms. Data on cumulative asbestos and smoking were available for all subjects. To assess gene-gene and gene-environmental interactions, logistic regression was used. The associations between MnSOD Ala −9Val polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…These results were supported by the evidence in a murine model that alveolar macrophages were able to produce nitrite products through an overexpression of iNOS if exposed to asbestos [ 78 ]. These preliminary findings were subsequently confirmed by more recent studies [ 79 , 80 ] and further enhanced by the observation that iNOS genetic polymorphisms could influence the risk of developing lung fibrosis in asbestos exposed patients [ 81 , 82 ]. No specific data have been published on the accuracy of eNO parameters in detecting the onset of lung fibrosis in asbestos-exposed patients or their prognostic value.…”
Section: Extended Feno Analysis In Ilds: Current Evidencesupporting
confidence: 55%
“…These results were supported by the evidence in a murine model that alveolar macrophages were able to produce nitrite products through an overexpression of iNOS if exposed to asbestos [ 78 ]. These preliminary findings were subsequently confirmed by more recent studies [ 79 , 80 ] and further enhanced by the observation that iNOS genetic polymorphisms could influence the risk of developing lung fibrosis in asbestos exposed patients [ 81 , 82 ]. No specific data have been published on the accuracy of eNO parameters in detecting the onset of lung fibrosis in asbestos-exposed patients or their prognostic value.…”
Section: Extended Feno Analysis In Ilds: Current Evidencesupporting
confidence: 55%
“… 24 , 25 , 26 Nevertheless, the interaction between asbestos exposure and genetic susceptibility due to genetic polymorphism of antioxidant enzymes has been shown for asbestosis. 27 We have previously described the association between SOD2 Ala/Ala genotype and asbestosis 28 as well as association between CAT -262 TT genotype and asbestosis. 16 Landi et al .…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that in addition to asbestos exposure, genetic factors may also affect the development of asbestos-related diseases (40)(41)(42). This study investigated the influence of NLRP3 rs35829419 and CARD8 rs2043211 polymorphisms on the risk of different asbestos-related diseases.…”
Section: Discussionmentioning
confidence: 99%